Islamic Republic of Mauritania : Sixth Review Under the Poverty Reduction and Growth Facility Arrangement and Request for Waiver of a Performance Criterion. (IMF Staff Country Reports; Country Report, 2003)
This paper focuses on the Islamic Republic of Mauritania's Sixth Review Under the Poverty Reduction and Growth Facility (PRGF) and a Request for Waiver of Performance Criterion. Performance under the PRGF-supported program remained strong in 2002. All the quantitative and structural performance criteria and benchmarks were met except for the publication of the audit of the central bank accounts, which was delayed for technical reasons. The IMF staff commends the authorities for bringing to a successful conclusion the current PRGF Arrangement and for their impressive record on macroeconomic stability and structural reforms.